2013
DOI: 10.1039/c3ta14409g
|View full text |Cite
|
Sign up to set email alerts
|

A versatile, industrially relevant, aqueous room temperature synthesis of HKUST-1 with high space-time yield

Abstract: A facile aqueous room temperature synthesis method has been developed to synthesize HKUST-1 from nano-materials to micro-and hierarchical porous structures by tuning either the copper source or the reaction time. The synthesis is readily scalable, with space-time yield >2000 kg m À3 day À1 .Scheme 1 One-pot synthetic routes to nano-, micro-and hierarchically porous HKUST-1 from a wholly aqueous reaction mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
97
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 23 publications
10
97
0
1
Order By: Relevance
“…After the conversion to MOF, the measured diffraction patterns matched with previouslyreported HKUST-1 diffraction patterns. 47 proposed by Bradshaw et al, 56 was found to have the surface area of 1236 m 2 g −1 . The surface areas of the HKUST-1 materials prepared using the method proposed here were found to be c.a.…”
Section: Resultsmentioning
confidence: 98%
“…After the conversion to MOF, the measured diffraction patterns matched with previouslyreported HKUST-1 diffraction patterns. 47 proposed by Bradshaw et al, 56 was found to have the surface area of 1236 m 2 g −1 . The surface areas of the HKUST-1 materials prepared using the method proposed here were found to be c.a.…”
Section: Resultsmentioning
confidence: 98%
“…The data yield a BET surface area of 1018 m 2 g À1 and a pore volume of 0.41 cm 3 g À1 (at p/p 0 ¼ 0.3) and 0.67 cm 3 g À1 at p/p 0 ¼ 0.99 consistent with other reports of HKUST-1 nanoparticles and networks. 26 In addition, the isotherm reveals an increased N 2 uptake at high relative pressure and a modest desorption hysteresis centred at 50 nm (BJH). This is indicative of intergrain textural mesoporosity arising from the small particles observed in SEM images (Fig.…”
Section: Nanoparticle Growth Of Hkust-1 By C 12 Guamentioning
confidence: 99%
“…However, HKUST-1 can be synthesized in an aqueous solution. Huo et al [102] proposed a novel facile and rapid room-temperature synthesis approach to prepare HKUST-1 through vigorous mixing of metal salt powder (cupric acetate anhydrous, Cu(OAC) 2 ) with excess ligand (benzene-1,3,5-tricarboxylic acid, H 3 BTC) using only water as the reaction solvent (Fig. 4).…”
Section: Irmof Seriesmentioning
confidence: 99%